Prison Family Engagement Policies: A Multistate Systematic Review and Content Analysis - Pappas, Laceé N. (The prison journal, 2024)
Opportunities for incarcerated persons to connect with their loved ones exist in several forms. Yet, there is limited evidence documenting the scope of state prison family engagement policies beyond visitation. To fill this gap, a systematic policy review and content analysis of nine state prison family engagement policies was conducted. The results provide evidence of both consistencies and inconsistencies in policies across forms of prison contact, as well as opportunities and barriers for incarcerated persons. Important policy and practice takeaways are discussed, particularly the need for more timely, transparent, and clear policies regarding family engagement in correctional settings.